Anticancer regimens containing third generation taxanes SB-T-121605 and SB-T-121606 are highly effective in resistant ovarian carcinoma model - Seborova, Karolina; Koucka, Kamila; Spalenkova, Alzbeta; Holy, Petr; Ehrlichova, Marie; Sychra, Tomas; Chen, Lei; Bendale, Hersh; Ojima, Iwao; Sandoval-Acuña, Cristian; Truksa, Jaroslav; Soucek, Pavel; et al. (Frontiers in Pharmacology, 2022)
Taxanes are widely used in the treatment of ovarian carcinomas. One of the main problems with conventional taxanes is the risk of development of multidrug resistance. New-generation synthetic experimental taxoids (Stony Brook Taxanes; SB-T) have shown promising effects against various resistant tumor models. The aim of our study was to compare the in vitro efficacy, intracellular content, and in vivo antitumor effect of clinically used paclitaxel (PTX) and SB-Ts from the previously tested second (SB-T-1214, SB-T-1216) and the newly synthesized third (SB-T-121402, SB-T-121605, and SB-T-121606) generation in PTX resistant ovarian carcinoma cells NCI/ADR-RES. The efficacy of new SB-Ts was up to 50-times higher compared to PTX in NCI/ADR-RES cells in vitro. SB-T-121605 and SB-T-121606 induced cell cycle arrest in G2/M phase much more effectively and their intracellular content was 10-15-times higher, when compared to PTX. Incorporation of SB-T-121605 and SB-T-121606 into the therapeutic regimens containing PTX were effective in suppressing tumor growth in vivo in NCI/ADR-RES based mice xenografts at small doses (≤3mg/kg), where their adverse effects were eliminated. In conclusion, new SB-T-121605 and SB-T-121606 analogs are promising candidates for the next phase of preclinical testing of their combination therapy with conventional taxanes in resistant ovarian carcinomas.